The Effect of East and West Seasonal Variability on Demersal Fish Recruitment Patterns in Coastal Waters of NTB - Rauhul Azmi; Budi Sentosa; Antoni Mujtaba (Journal of Marine Fisheries, 2026)
This study analyzes the influence of east monsoon and west monsoon variability on demersal fish recruitment in coastal waters of West Nusa Tenggara. Climate-driven oceanographic changes strongly regulate fish recruitment dynamics in tropical and temperate systems. Recruitment variability is linked to larval survival, hydrodynamics, and temperature fluctuations. This research uses a multi-source approach combining catch data, larval abundance records, and climate indices during 2010–2024. The results show that the west monsoon period increases nutrient input and larval abundance, while the east monsoon strengthens upwelling and redistributes juvenile fish stocks. Recruitment peaks occur during transitional seasons when environmental stability improves. Similar patterns of climate-driven recruitment shifts have been documented in other marine ecosystems. The study concludes that seasonal variability is a dominant driver of demersal fish recruitment in NTB waters, with implications for fisheries management under climate change scenarios